2021
DOI: 10.1093/jac/dkab376
|View full text |Cite
|
Sign up to set email alerts
|

Large diversity of linezolid-resistant isolates discovered in food-producing animals through linezolid selective monitoring in Belgium in 2019

Abstract: Background Linezolid is a critically important antibiotic used to treat human infections caused by MRSA and VRE. While linezolid is not licensed for food-producing animals, linezolid-resistant (LR) isolates have been reported in European countries, including Belgium. Objectives To: (i) assess LR occurrence in staphylococci and enterococci isolated from different Belgian food-producing animals in 2019 through selective monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
2
23
3
Order By: Relevance
“…In contrast, other authors obtained non-resistant isolates of this ST from environmental samples [ 53 ]. Conversely, other works have reported ST22 isolates obtained from human and animal sources as optrA carriers [ 54 ], while our ST22 isolates were not phenotypically resistant nor did they carry any ARG. Regarding the only VG found in E. faecium , the acm gene, this has recently been described in clinical strains of patients with endocarditis, indicating pathogenic potential.…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast, other authors obtained non-resistant isolates of this ST from environmental samples [ 53 ]. Conversely, other works have reported ST22 isolates obtained from human and animal sources as optrA carriers [ 54 ], while our ST22 isolates were not phenotypically resistant nor did they carry any ARG. Regarding the only VG found in E. faecium , the acm gene, this has recently been described in clinical strains of patients with endocarditis, indicating pathogenic potential.…”
Section: Discussioncontrasting
confidence: 96%
“…Two earlier reports on cfr in CC398 from Spain and Belgium also were from a pig farmer and from a person with professional contact with pigs and cows 39 , 40 . A recent study on linezolid-resistant isolates from food-producing animals in Belgium included the analysis of six ST398 S. aureus isolates that all carried the cfr gene 42 . These studies support the hypothesis that the cfr gene likely originates from animals.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NWT isolates for erythromycin, a 14-membered macrolide, was quite high (15,23). However, recent studies on animal samples inoculated onto linezolid-supplemented media revealed that linezolid-resistant enterococci (or staphylococci) may be frequently present although not detected when analysing only strains from the dominant enterococci population isolated on non-supplemented media (28). Linezolid has never been used in animal production, but antimicrobial resistance mechanisms evidenced in animal isolates (e.g.…”
Section: Discussionmentioning
confidence: 99%